Photonic crystals for perovskite‐based optoelectronic applications. Issue 1 (24th May 2021) - Yang, Xia; Yang, Hanjun; Hu, Xiaotian; Li, Fangfang; Yang, Zhou
Abstract: The emerging perovskite materials present great opportunities for cost‐saving and efficient optoelectronic devices. However, there are still some roadblocks in the path toward commercialization of perovskite‐based devices, such as low light utilization, poor crystalline quality and dissatisfactory environmentally long‐time stability. To solve these problems, photonic crystal (PC) as a promising structure for control light has been exploited. To date, a series of perovskite‐based devices improved by PC has been reported. These PCs do not only improve the performance of devices but also give flexural endurance, vivid color and some degree of transparency to the electronic devices. Herein, a general overview is provided on the recent advances for the application of PCs in perovskite‐based optoelectronic devices (solar cells, photodetectors, and light‐emitting diodes). In addition, some personal perspectives on potential future challenges and improvements in this field are presented. Abstract : As a key factor affecting the performance and stability of the perovskite optoelectronic device, optical design can simultaneously enhance the light trapping, prolong the optical path length, improve the perovskite film quality and release the residual stress. This review summarizes the applications of bio‐inspired structures, photonic crystals in the perovskite‐based optoelectronic files, and its commercial feasibility prospects.